A Study of Awareness of ‘Open Book Examination’ System - Sikdar, Mandira; Amraotkar, Swati (JOURNAL OF INDIAN EDUCATION, 2012)
Very few issues are likely to have a crucial impact on the future as the training and education of ‘human resources’. The quality of education imparted assumes extraordinary significance in this context–What are the goals of education today and are our current educational practices in conformity to the same? Today, Education, while not losing sight of its traditional goals (reading, writing, arithmetic), will also have to equip individuals to live effectively in the ‘knowledge society’, i.e. acquire relevant knowledge and inculcate and interpret new values that will in turn guarantee them the ability to keep pace with the evolution of their environment. Our schools and educational institutions must conform to this emerging reality-via the designing of appropriate instructional processes and evaluation systems that gauge the intellectual growth of students and not merely their ability to memorise information and regurgitate. Unfortunately, our Educational practices and systems of examination have not been able to keep pace with the changing context-they still highlight the importance of rote memorisation, fail to test higher order skills like critical thinking, reasoning, etc., and are largely inflexible with no allowance made for different learners. What is needed urgently is examination reform wherein there is a shift in emphasis to testing competencies, understanding of concepts taught, and development of creative and critical thinking abilities. Although efforts towards reforming examination system are started, i.e, continuous comprehensive evaluation and making examination optional at secondary grade. However, some more innovations/alternatives need to be tried in Indian Education System which caters to tremendous diversity of the country. In view of the aforementioned, Open Book Examination (OBE) could be a significant alternative assessment system that could be implemented keeping in mind